Erlotinib eradicates brain metastases from epidermal growth factor receptor mutant non-small cell lung cancer - Jabbari, Siavash; Pins, Michael; Kruczek, Kimberly; Nabhan, Chadi (Avicenna Journal of Medicine, 2011)
Erlotinib is active in patients with lung cancer; especially those who demonstrate a mutation in exons 18-21 in the epidermal growth factor receptor (EGFR) gene. Patients with lung cancer and brain metastases have poor prognosis as systemic chemotherapy is ineffective in treating the central nervous system (CNS) metastases due to its inability to cross the blood brain barrier. Herein, we report a case of a 61 year old female who presented with stage IV adenocarcinoma of the lung with bilateral cerebral and cerebellar CNS involvement. The patient′s tumor harbored a mutation in exon 19 in the EGFR gene. Treatment with erlotinib was started as soon as the molecular studies were available with remarkable and complete radiographic response in the CNS disease, and complete resolution of the previously detected metastases. The patient did not receive any other CNS intervention and radiation was not given due to the lack of CNS symptoms.
Keywords: Brain metastasis; Erlotinib; lung cancer; tarceva